Chemical sterilization and other control measures for the commission of sexual crimes - Alonso Sandoval, Tomás Cristobal (Cuadernos de dereito actual, 2021)
A subject that reverts to the current debate on criminal penalties for offenders who commit sex crimes is chemical or surgical sterilization. This issue has generated strong discussions in the past and its questioning does not seem to have been satisfactorily resolved. Is it a return to cruel and inhuman punishment? Can it be considered a mutilation? Are they a violation of the human rights of those deprived of liberty? To these questions and their possible consequences, of the application of this penal sanction, it is necessary to find a legal solution, taking into consideration the doctrine, the legislation both national and international and, above all, the jurisprudence, although Scarce, which will provide us with lights on its possible application.
Keywords: human rights; sexual offences; chemical sterilization; penal law; fundamental rights; Emerging